The Effect of Experimental Methods with an Inductive Approach on the Students’ Physics Scientific Performance (Jurnal Pendidikan Fisika, 2021)
Science is concerned with how to understand nature systematically so that it is not only limited to mastering a collection of knowledge in the form of facts or concepts, but also as a process of discovery. An inductive approach can help students gather information and test it thoroughly, process information into concepts, and learn to manipulate these concepts. The aim of this study were 1) to describe the scientific performance of class VIII students of one of the schools in Bulukumba who were taught by using the experimental method with the Inductive Approach, 2) to describe the scientific performance of class VIII students of one of the schools in Bulukumba who were taught using conventional learning methods, 3) analyzing the scientific performance of class VIII students of one of the schools in Bulukumba which was higher. This research is a type of experimental research, with posttest design only control group design. The population in this study were all students of class VIII of one of the schools in Bulukumba which were divided into six classes. The sample in this study were students of class VIII1 as the experiment class and class VIII2 as the control class who were selected by class randomization technique. The instrument used in this study was the scientific performance test. The results showed that 1)the scientific performance of class VIII students of one of the schools in Bulukumba who were taught using the experimental method with the inductive approach was in the very high category, 2)the scientific performance of class VIII students of one of the schools in Bulukumba who were taught using conventional methods were in the medium category, and 3) the physics scientific performance of class VIII students of one of The schools in Bulukumba who were taught using the experimental method with an Inductive Approach was higher than those taught using the conventional method. The recommendation of this research is that inductive learning should be carried out on a broader scale, namely in other schools, especially in physics learning.
Keywords: scientific performance; experimental methods; physics learning; inductive approach